Numa y la construcción poética de la historia en las metamorfosis de Ovidio - Martínez Astorino, Pablo (Quaderni urbinati di cultura classica.)
The deliberate terminological link between the image of Numa and the man created as a sanctius animal (Met. 1, 76) characterizes Numa as one of the few heroes in the work who makes the initial, paradigmatic condition of sanctius animal prevail. Numa?s relationship with Pythagoras, another sanctius animal, lies in the motif of pax, a feature of the Golden Age that Pythagoras shows as an ideal one and Numa fullfils in his reign. However, the image of pax does not isolate Numa by turning him into a representative of a counterfactual Roma altera; intratext lets us realize that this image consolidates in Augustus, even in a work devoted to Greek tradition. Yet the end is not political: it is the poet, showed as higher than the princeps in the sphragis, the author of this representation which ends in Augustus